Long Non-coding RNA DANCR as an Emerging Therapeutic Target in Human Cancers - Jin, Shi-Jia; Jin, Ming-Zhu; Xia, Bai-Rong; Jin, Wei-Lin (Frontiers in Oncology, 2019)
Long noncoding RNAs (lncRNAs) are emerging as important regulators of numerous biological processes, especially in cancer development. Aberrantly expressed and specifically located in tumor cells, they exert distinct functions in different cancers via regulating multiple downstream targets such as chromatins, RNAs and proteins. Differentiation antagonizing nonprotein coding RNA (DANCR) is a cytoplasmic lncRNA that generally works as a tumor promoter. Mechanically, DANCR promotes the functions of vital components in the oncogene network by sponging their corresponding microRNAs or by interacting with various regulating proteins. DANCR’s distinct expression in tumor cells and collective involvement in pro-tumor pathways make it a promising therapeutic target for broad cancer treatment. Herein, we summarize the functions and molecular mechanism of DANCR in human cancers. Furthermore, we introduce the use of CRISPR/Cas9, antisense oligonucleotides and small interfering RNAs as well as viral, lipid or exosomal vectors for onco-lncRNA targeted treatment. Conclusively, DANCR is a considerable promoter of cancers with a bright prospect in targeted therapy.